Analysis of The Effect of Promotion on the Sales of General Insurance Services at PT. Wahana Tata Insurance - Hero Wirasmara Kusuma (The Institute of Academic Research and Publication (IARP), 2021)
This study aims 1) to determine the implementation of promotions carried out by PT. Wahana Tata Insurance, 2) to determine the relationship between promotions and company sales, 30 to find out how much the contribution of promotional costs affects sales results, and 4) how big the role or influence caused by the implementation of promotions to increase sales volume. This study uses primary data from company reports and direct observations of the company's operational activities. The study used simple linear regression analysis and the regression coefficient significance test. The study results indicate that from the calculation of correlation analysis, the correlation coefficient is positive at 0.87, which means that the relationship between promotional costs and company sales results is very strong and positive. The calculation of the determinant coefficient analysis shows that promotional activities' contribution to the company's sales results is 75.69%, which means that the contribution of promotional costs is very significant to the company's sales results. From the correlation significance test, the t value is 3.057, greater than the t-table of 2.353, which means that the relationship between the promotion costs and sales results is strong and significant. And from the calculation of the simple linear regression analysis and the regression coefficient signification test, it is known that the t-count is 3.022, when compared to the t-table is 2.353. This is concluded that t-count is greater than t-table, which means that there is a strong and significant influence between promotion costs and sales results